Retinoblastoma: Etiology, Modeling, and Treatment - Kaewkhaw, Rossukon (Cancers (Basel), 2020)
Retinoblastoma is a retinal cancer that is initiated in response to biallelic loss of RB1 in almost all cases, together with other genetic/epigenetic changes culminating in the development of cancer. RB1 deficiency makes the retinoblastoma cell-of-origin extremely susceptible to cancerous transformation, and the tumor cell-of-origin appears to depend on the developmental stage and species. These are important to establish reliable preclinical models to study the disease and develop therapies. Although retinoblastoma is the most curable pediatric cancer with a high survival rate, advanced tumors limit globe salvage and are often associated with high-risk histopathological features predictive of dissemination. The advent of chemotherapy has improved treatment outcomes, which is effective for globe preservation with new routes of targeted drug delivery. However, molecularly targeted therapeutics with more effectiveness and less toxicity are needed. Here, we review the current knowledge concerning retinoblastoma genesis with particular attention to the genomic and transcriptomic landscapes with correlations to clinicopathological characteristics, as well as the retinoblastoma cell-of-origin and current disease models. We further discuss current treatments, clinicopathological correlations, which assist in guiding treatment and may facilitate globe preservation, and finally we discuss targeted therapeutics for future treatments.